Dampak Hubungan Karyawan dan Kedisiplinan Kerja terhadap Kinerja Karyawan - Rizki Akbari; Kokom Komariah; Dicky Jhoansyah (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study was to determine the impact of employee relations (variable X1) and Work Discipline (variable X2) on Employee Performance (variable Y). The method used in this research is to use descriptive and associative methods. Data collection techniques used by researchers in this study are through observation, questionnaire interviews, documentation and literature studies. The data analysis technique used is the validity test, reliability test, multiple linear regression analysis, including the test of the coefficient of determination and multiple correlation coefficients. The results of the test of the coefficient of determination seen from the value (Adjusted R2) of 0.531 can be interpreted that the impact of employee relations and working discipline on employee performance is equal to 53.1%. The remaining 46.9% is influenced by other factors outside this study. Conclusion, there is a moderate relationship between employee relations and work discipline with employee performance. Keywords: Employee Relations, Work Discipline, Employee Performance